Portfolios in university foreign language courses: student’s perception - Keim Cubas, Lucrecia (Didáctica. Lengua y Literatura, 2013)
In the last ten years has been written and thought a lot on the use of portfolios in language classes. However, it has not yet been adequately studied how students perceive the use of these portfolios. This article presents some of the results of the project Design and study of the impact of tools for the development of strategic competence in foreign language learning in a university context (DEICOMECU). Specifically the article focuses on the perceptions of students regarding the use of portfolios. It includes a description of the context and type of portfolios that are used and the author’s reflections after a subsequent re-reading of the interpretations of the data.